INDICATOR PHYSICAL FITNESS USING NORMAL AND OVERWEIGHT BODY MASS INDEX MEASUREMENT METHOD IN STUDENTS - Revina Dwi Putri Talenta Sitompul, Evelin Malinti (SABDA EDU PRESS (SEP), 2024)
Background. Everyone should place a high premium on physical fitness because a fit body allows one to perform everyday chores and responsibilities at their best. Body mass index, which measures dietary status, is one element that affects physical fitness. (BMI). This study intends to assess the physical health and BMI of students at the Adventist University of Indonesia's Faculty of Nursing. With Spearman's rho test, this study technique is quantitative. There were 70 participants who voluntarily and consciously gave their consent. The Zuchora Physical Fitness Test, height measuring equipment, and weight scales were the research tools employed. Results: A significant negative connection between BMI and physical fitness, speed, and arm strength was found using the Spearman Rho test (p.05). Jumping ability, flexibility, endurance, and muscle strength did not have a significant association with BMI (p > 0.05), however. The findings of this study suggest that BMI has an impact on physical fitness in terms of arm speed and strength. The speed and arm strength decrease as BMI increases.